The Attitude of Youth to Alcohol: the Risk of Alcohol Dependence - Elina Hlavinska (Проблеми сучасної психології, 2022)
The purpose of this article is: to reveal the psychological aspects of some diseases, as a result of alcohol consumption; to describe the peculiarities of physical dependence in a way of alcoholic state; to make a scheme how alcoholism is developed; to describe the characteristic complications of binge drinking, such as white fever, alcoholic delirium; to model the degrees of intoxication; to provide the pilot research and to find out the attitude of youth to alcohol.